2014
DOI: 10.1210/jc.2014-1069
|View full text |Cite
|
Sign up to set email alerts
|

Higher 25(OH)D2 Is Associated With Lower 25(OH)D3 and 1,25(OH)2D3

Abstract: In a cohort of older men, 25(OH)D2 is associated with lower levels of 25(OH)D3 and 1,25(OH)2D3, suggesting that vitamin D2 may decrease the availability of D3 and may not increase calcitriol levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
23
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 30 publications
8
23
1
Order By: Relevance
“…Variables most likely to affect the above associations were used in base and multivariable models and parallel those used in previous MrOS analyses for 25OHD and skeletal outcomes . We previously evaluated the relationships between vitamin D metabolites in this cohort and found that the amount of supplementation was minimal and did not significantly affect the associations of vitamin D metabolites . Therefore, these analyses were not adjusted for vitamin D supplement use.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…Variables most likely to affect the above associations were used in base and multivariable models and parallel those used in previous MrOS analyses for 25OHD and skeletal outcomes . We previously evaluated the relationships between vitamin D metabolites in this cohort and found that the amount of supplementation was minimal and did not significantly affect the associations of vitamin D metabolites . Therefore, these analyses were not adjusted for vitamin D supplement use.…”
Section: Methodssupporting
confidence: 82%
“…Aliquots of a single‐serum pool were included in alternate assay runs. Using the pooled serum, the interassay coefficients of variation (CVs) for 25OHD 2 and 25OHD 3 were both 4.4%, and the intra‐assay CVs were 6.4% and 4.9%, respectively . This assay does not cross‐react with 24‐hydroxy‐ or 26‐hydroxy‐derivatives.…”
Section: Methodsmentioning
confidence: 98%
“…It might also reflect our finding that supplementation with vitamin D 2 led to a decrease in 25(OH)D 3 concentrations, as also observed in non‐trial settings by others , while supplementation with vitamin D 3 did not affect 25(OH)D 2 concentrations in the present trial. The decrease in 25(OH)D 3 concentrations in the D 2 group may suggest different bioavailability , possible more rapid metabolism or clearance of circulating 25(OH)D 3 following D 2 supplementation, or competition for enzymatic activity by CYP2R1 for 25‐hydroxylation of vitamin D 2 and D 3 . It has been suggested that an upregulation in mechanisms required to metabolize D 2 and its metabolites may increase the degradation of circulating 25(OH)D 3 concentrations but the biological significance of these changes is currently unclear.…”
Section: Discussionsupporting
confidence: 91%
“…This may be partially attributable to the shorter half‐life of 25(OH)D 2 versus 25(OH)D 3 in the circulation, which is related to the lower affinity of the D 2 metabolite for the vitamin D‐binding protein . It might also reflect our finding that supplementation with vitamin D 2 led to a decrease in 25(OH)D 3 concentrations, as also observed in non‐trial settings by others , while supplementation with vitamin D 3 did not affect 25(OH)D 2 concentrations in the present trial. The decrease in 25(OH)D 3 concentrations in the D 2 group may suggest different bioavailability , possible more rapid metabolism or clearance of circulating 25(OH)D 3 following D 2 supplementation, or competition for enzymatic activity by CYP2R1 for 25‐hydroxylation of vitamin D 2 and D 3 .…”
Section: Discussionsupporting
confidence: 77%
“…25‐OH D3 and 1,25‐(OH)2 D3 correlate in patients without PHPT . However, elevated levels of iPTH increase the metabolism of 25‐OH D3‐1,25‐(OH)2 D3 by directly activating 1α‐hydroxylase.…”
Section: Discussionmentioning
confidence: 99%